The revenue implication of trade liberalisation in Sub-Saharan Africa: Some new evidence - Lanre Kassim (University of Kent, School of Economics, 2016)
Despite the advent of trade liberalisation, trade taxes still remain a huge source of tax revenues in Sub-Saharan Africa. Further trade reforms in the form of the Economic Partnership Agreements (EPAs) could, however, hinder output growth in the region if these reforms lead to a decline in total tax revenues. Motivated by this conundrum, our paper adopts panel data estimators to investigate the impact of trade liberalisation on total tax revenue across 28 Sub-Saharan African countries from 1981 to 2010. We also analysed the impact of freer trade policies on trade and domestic tax revenues. The results indicate that trade liberalisation is associated with an increase in total tax revenues. Also, the reduction of trade tariffs significantly increases and decreases domestic and trade tax revenues, respectively. In addition, greater urbanisation is associated with an increase in total tax revenues while a higher inflation rate decreases tax revenues.
Keywords: C23; F13; F14; H20; O55; 330; Trade liberalisation; Generalised method of moments; Fixed effects; Tax revenue; Sub-Saharan Africa